Uncoupling N-acetylaspartate from brain pathology: implications for Canavan disease gene therapy - Jonquières, Georg von; Schneider, Miriam (Acta neuropathologica, 2018)
N-Acetylaspartate (NAA) is the second most abundant organic metabolite in the brain, but its physiological significance remains enigmatic. Toxic NAA accumulation appears to be the key factor for neurological decline in Canavan disease—a fatal neurometabolic disorder caused by deficiency in the NAA-degrading enzyme aspartoacylase. To date clinical outcome of gene replacement therapy for this spongiform leukodystrophy has not met expectations. To identify the target tissue and cells for maximum anticipated treatment benefit, we employed comprehensive phenotyping of novel mouse models to assess cell type-specific consequences of NAA depletion or elevation. We show that NAA-deficiency causes neurological deficits affecting unconscious defensive reactions aimed at protecting the body from external threat. This finding suggests, while NAA reduction is pivotal to treat Canavan disease, abrogating NAA synthesis should be avoided. At the other end of the spectrum, while predicting pathological severity in Canavan disease mice, increased brain NAA levels are not neurotoxic per se. In fact, in transgenic mice overexpressing the NAA synthesising enzyme Nat8l in neurons, supra-physiological NAA levels were uncoupled from neurological deficits. In contrast, elimination of aspartoacylase expression exclusively in oligodendrocytes elicited Canavan disease like pathology. Although conditional aspartoacylase deletion in oligodendrocytes abolished expression in the entire CNS, the remaining aspartoacylase in peripheral organs was sufficient to lower NAA levels, delay disease onset and ameliorate histopathology. However, comparable endpoints of the conditional and complete aspartoacylase knockout indicate that optimal Canavan disease gene replacement therapies should restore aspartoacylase expression in oligodendrocytes. On the basis of these findings we executed an ASPA gene replacement therapy targeting oligodendrocytes in Canavan disease mice resulting in reversal of pre-existing CNS pathology and lasting neurological benefits. This finding signifies the first successful post-symptomatic treatment of a white matter disorder using an adeno-associated virus vector tailored towards oligodendroglial-restricted transgene expression.
Published online: 7 November 2017
Gesehen am 24.07.2018